Pseudopaludicola ternetzi (Anura: Leiuperidae): two lectotypes for the same taxon - Cardozo, Dario; Baldo, Diego (Zootaxa, 2012)
Pseudopaludicola ternetzi was described on the basis of an undefined number of syntypes, but involving males and females (Miranda-Ribeiro 1937). Since Miranda-Ribeiro described this species, several taxonomic considerations were made on it. First, Bokermann (1966) considered P. ternetzi as a synonym of P. ameghini (Cope 1887), without giving any evidence to support this decision. Although some authors followed this proposal (like Gallardo 1968), others continued considering P. ternetzi as a good species (e.g., Frost 1985; Lynch 1989). Haddad and Cardoso (1987) provided bioacustic and morphometric evidence to consider P. ameghini as a junior synonym of P. mystacalis (Cope 1887). In 1996, Lobo reviewed the type specimens of P. ameghini, P. mystacalis, and P. saltica described by Cope (1887) and housed at the ANSP (Academy of Natural Sciences of Philadelphia), and redescribed P. ternetzi based on four vouchers collected by Dr. Ternetz in December of 1923, deposited in the Museu Nacional, Rio de Janeiro, Brazil (MNRJ). In coincidence with Haddad and Cardoso (1987), Lobo (1996) considered P. ameghini as a junior synonym of P. mystacalis, assigned a lectotype for P. ternetzi (MNRJ 5462, male), and designated as paralectotypes the vouchers MNRJ 477, MNRJ 5460, and MNRJ 5461 (all females). Lobo choose the only male syntype examined by him as lectotype considering that the detailed description by Miranda-Ribeiro (1937) of a male matched with the size and morphology of this specimen, while only reported some details of a female. Such taxonomic decision was based on the article 74 of the International Code of Zoological Nomenclature (ICZN 1985).